1995
DOI: 10.1109/77.402798
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of transport properties normal and parallel to the tape plane in Bi-2223/Ag tapes

Abstract: We have performed transport, resistivity and critical current measurements on Bi-2223/Ag tapes with current directions both parallel and perpendicular to the tape plane in magnetic fields up to 7 T and 50cTc250 K. We find that the resistivity along the tape normal (nominal c-axis in a textured tape) is metallic, scales with the in-plane resistivity at all fields and is dramatically reduced from single crystal c-axis values. Similarly, the critical current along the tape normal exhibits magnetic field and field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A pronounced role of grain boundaries in charge transport phenomena is simply a consequence of the high effective resistivity of a boundary, compared with the resistivity of the volumetrically predominant and, on averaging, homogeneous intragranular background. This qualitative relationship between the intragranular and grain boundary resistivities, documented to exist both in YBCO and in BSCCO systems [50,73,75] has been pointed out in numerous reports as a plausible source of the inhomogeneous distribution of normal and superconducting currents. In particular, it has frequently been suggested that the actual current lines bypass all high-angle boundaries, or boundaries substantially degraded by other causes, owing to their high resistances (decisive for normal transport) or because of their small Josephson critical currents (decisive for supercurrent transport).…”
Section: Current Transfer In High-t C Superconductors: Global Aspectsmentioning
confidence: 62%
“…A pronounced role of grain boundaries in charge transport phenomena is simply a consequence of the high effective resistivity of a boundary, compared with the resistivity of the volumetrically predominant and, on averaging, homogeneous intragranular background. This qualitative relationship between the intragranular and grain boundary resistivities, documented to exist both in YBCO and in BSCCO systems [50,73,75] has been pointed out in numerous reports as a plausible source of the inhomogeneous distribution of normal and superconducting currents. In particular, it has frequently been suggested that the actual current lines bypass all high-angle boundaries, or boundaries substantially degraded by other causes, owing to their high resistances (decisive for normal transport) or because of their small Josephson critical currents (decisive for supercurrent transport).…”
Section: Current Transfer In High-t C Superconductors: Global Aspectsmentioning
confidence: 62%
“…The anisotropy of a material can be expressed in terms of thermal conductivity and electrical resistivity with tensors {λ uv } and {ρ uv }(J), u, v = 1, 2, 3 [33][34][35].…”
Section: Physical Backgroundmentioning
confidence: 99%
“…Data for the resistivity of silver were found in [49]. For the resistivity of the Bi-2223 material, we used equation ( 8) with ρ r (T ) = 10 µ m [35]. J (T ) and J r (T ) were found by fitting equation (8) to the power law, equation (7), with n = 10 in the interval 0.7J c (T ) J 1.2J c (T ).…”
Section: Example Runsmentioning
confidence: 99%
“…1 field. Earlier 1G tapes have been tested at various temperatures in both field directions [7,8]. Angular measurements on 2G have been performed at higher temperatures [9,10].…”
Section: Introductionmentioning
confidence: 99%